Philosophical relativity - Unger, Peter K. (B. Blackwell, 1984)
In this short volume, Peter Unger questions the objectives answers that have been given to traditional problems in philosophy. He casts doubt on the generally unquestioned view that fundamental questions pertaining to meaning and existence have direct solutions, arguing that by their very nature they remain ultimately unanswerable.